1994
DOI: 10.1007/bf02245454
|View full text |Cite
|
Sign up to set email alerts
|

Controlled comparison of milnacipran and fluoxetine in major depression

Abstract: The efficacy and the tolerance of milnacipran (100 mg/day), a second generation antidepressant which equipotently inhibits both noradrenaline and serotonin reuptake, was compared to fluoxetine (20 mg/day), a selective serotonin reuptake inhibitor, in two parallel groups of, respectively, 97 and 93 major depressive outpatients. The duration of the study was 6 weeks, with assessments every 2 weeks by means of the Montgomery and Asberg depression scale (MADRS), the Hamilton depression scale, the clinical global i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
24
0
3

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 18 publications
0
24
0
3
Order By: Relevance
“…Most of them show no difference in efficacy [15][16][17][18] . One study show an SSRI (fluoxetine) with more efficacy than minalcipran 19 , while another the opposite 11 . A recent meta-analysis 20 concluded that milnacipran and SSRIs do not differ with respect to the overall efficacy in the treatment of MDD.…”
Section: Introductionmentioning
confidence: 99%
“…Most of them show no difference in efficacy [15][16][17][18] . One study show an SSRI (fluoxetine) with more efficacy than minalcipran 19 , while another the opposite 11 . A recent meta-analysis 20 concluded that milnacipran and SSRIs do not differ with respect to the overall efficacy in the treatment of MDD.…”
Section: Introductionmentioning
confidence: 99%
“…В 1994 г. бельгийские иссле-дователи обследовали 190 больных, страдающих «большой депрессией». Авторы пришли к заключению, что 6-недель-ная терапия флуоксетином (20 мг/сут) более эффективна, чем применение милнаципрана (100 мг/сут) [22]. Француз-ские психиатры в 1998 г. провели исследование на материа-ле 289 больных эндогенной депрессией.…”
unclassified
“…[4][5][6][7][8] In fact, cyclopropane rings have already been successfully used to restrict the bioactive conformations of neurotransmitters, 4,5) amino acids, 6) peptides 7) and nucleosides. 8) We devised a new method for restricting the conformation of compounds having a cyclopropane ring, [9][10][11] and applied it to the design of the conformationally restricted analogs of [12][13][14][15][16] a clinically efficient antidepressant having a cyclopropane structure, to develop efficient NMDA (N-methyl-D-aspartic acid) receptor antagonists. [17][18][19][20][21][22][23][24][25] The structures of the conformationally restricted analogs are shown in Fig.…”
mentioning
confidence: 99%
“…Design and Pharmacological Effect of PPDC Milnacipran, which shows a potent antidepressant effect due to competitive inhibition of the re-uptake of serotonin (5-HT) in the central nervous system (CNS), [12][13][14][15][16] is also recognized as a non-competitive NMDA receptor antagonist. 35) Although the binding affinity of (Ϯ)-1 for the NMDA receptor is not high, the compound has the advantage of sufficiently pene- trating into the brain without serious side effects, 15,16) making it a clinically useful antidepressant and therefore a good lead for an efficient NMDA receptor antagonist.…”
mentioning
confidence: 99%
See 1 more Smart Citation